ESPGHAN Position Paper on Management and Follow-up of Children and Adolescents With Celiac Disease. Issue 3 (27th June 2022) - Mearin, Maria Luisa; Agardh, Daniel; Antunes, Henedina; Al-toma, Abdul; Auricchio, Renata; Castillejo, Gemma; Catassi, Carlo; Ciacci, Carolina; Discepolo, Valentina; Dolinsek, Jernej; Donat, Ester; Gillett, Peter; et al.
Abstract : There is a need for consensus on the recommendations for follow-up of children and adolescents with celiac disease. Objectives: To gather the current evidence and to offer recommendations for follow-up and management. Methods: The Special Interest Group on Celiac Diseases of the European Society of Paediatric Gastroenterology Hepatology and Nutrition formulated ten questions considered to be essential for follow-up care. A literature search (January 2010–March 2020) was performed in PubMed or Medline. Relevant publications were identified and potentially eligible studies were assessed. Statements and recommendations were developed and discussed by all coauthors. Recommendations were voted upon: joint agreement was set as at least 85%. Results: Publications (n = 2775) were identified and 164 were included. Using evidence or expert opinion, 37 recommendations were formulated on: The need to perform follow-up, its frequency and what should be assessed, how to assess adherence to the gluten-free diet, when to expect catch-up growth, how to treat anemia, how to approach persistent high serum levels of antibodies against tissue-transglutaminase, the indication to perform biopsies, assessment of quality of life, management of children with unclear diagnosis for which a gluten-challenge is indicated, children with associated type 1 diabetes or IgA deficiency, cases of potential celiac disease, which professionals should perform follow-up, how to improve the communication to patients and their parents/caregivers and transition from pediatric to adult health care. Conclusions: We offer recommendations to improve follow-up of children and adolescents with celiac disease and highlight gaps that should be investigated to further improve management.